Retinoic acid signaling regulates late stages of semicircular canal morphogenesis and otolith maintenance in the zebrafish inner ear. Issue 11 (2nd July 2022) - Mackowetzky, Kacey; Dicipulo, Renée; Fox, Sabrina C.; Philibert, Danielle A.; Todesco, Hayley; Doshi, Jainil D.; Kawakami, Koichi; Tierney, Keith; Waskiewicz, Andrew J.
Abstract: Background: The vitamin A derivative all‐trans retinoic acid (RA) regulates early stages of inner ear development. As the early disruption of the RA pathway results in profound mispatterning of the developing inner ear, this confounds analyses of specific roles in later stages. Therefore, we used the temporal‐specific exposure of all‐trans RA or diethylaminobenzaldehyde to evaluate RA functions in late otic development. Results: Perturbing late RA signaling causes behavioral defects analogous to those expected in larvae suffering from vestibular dysfunction. These larvae also demonstrate malformations of the semi‐circular canals, as visualized through (a) use of the transgenic strain nkhspdmc12a, a fluorescent reporter expressed in otic epithelium; and (b) injection of the fluorescent lipophilic dye DiI. We also noted the altered expression of genes encoding ECM proteins or modifying enzymes. Other malformations of the inner ear observed in our work include the loss or reduced size of the utricular and saccular otoliths, suggesting a role for RA in otolith maintenance. Conclusion: Our work has identified a previously undescribed late phase of RA activity in otic development, demonstrating that vestibular defects observed in human patients in relation to perturbed RA signaling are not solely due to its early disruption in otic development. Key Findings: Perturbations of retinoic acid signaling result in circling behavior Late embryo treatment of embryos with RA or RA‐blockers causes alteration of gene expression in the ear Alteration of RA signaling causes morphological changes to the semicircular canal system.